COST EFFECTIVENESS ANTARA BLOK KAUDAL DAN KETOROLAC INTRAVENA SEBAGAI ANALGESIA EARLY PERIOD POST OPERASI PADA PASIEN PEDIATRIK YANG MENJALANI OPERASI SEGMEN BAWAH UMBILICUS DENGAN DERAJAT NYERI SEDANG - , Juni Kurniawaty, Dr. H. Muhdar Abubakar, SpAn.KIC ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Postoperative pain in pediatric patients is often ineffectively treated. Ineffectively treated pain would cause abnormal psychological, physiological and behavioral effects. Adequate low cost post operative analgesia procedure in children is very important and can be obtained through various techniques, some of which are caudal block and iv ketorolac. Caudal block provides excellent analgesia because it has central effect. Methods: This research used double blind randomized clinical trials. The scope of this research included pediatric patients who underwent surgery below the umbilicus segment with moderate degree of pain using general anesthesia in GBST RSUP DR. Sardjito. Subjects covered 70 patients who met inclusion criteria, which were divided into two groups consisting of 35 patients each. Group C received caudal block with 0.125% bupivacain 1 ml/kgBW and group K received ketorolac 0.5 mg/kgBW. Subjects were pediatric patients, aged 2-6 years, ASA physical status I and II. Inclusion criteria: Duration of operation less than 120 minutes, with the degree of postoperative moderate. Exclusion criteria: contraindication to caudal block performed, a history of allergy to NSAIDs, bupivacaine and medications used, asthma, a history of analgesia in a long time, peptic ulceration, gastrointestinal bleeding, previous use of anticoagulants, renal failure, liver disease, previous use of NSAIDs (<24 hours), chronic pain syndrome. Results: Caudal block with bupivacaine 0.125% have a better effectiveness at minute 0 (27/8 vs 10/25) and 15 (34/1 vs 18/17), but has a lower effectiveness on the third hour (p = 0.031) compared with ketorolac 0.5 mg/kgBW iv. At minute 30, 45, 60 and 2 hours, they have the same effectiveness (p> 0.05), but the costs incurred in the caudal group was higher than iv ketorolac group (95.860Â±5.745 vs 17.200Â±14.886) (p = 0.000). The need of rescue analgesia between the two groups shows a significant difference. Where in the first hours ketorolac group require more morphine than ketorolac (p = 0.000), while the need for rescue analgesia in the next period (3 hours after surgery) caudal group requires more paracetamol syrup than the caudal group (p = 0.017) with the same side effect (p = 0.555). Conclusion : Caudal block is not cost effective than iv ketorolac in reducing pain in early postoperative period in pediatric patients undergoing surgery below the umbilicus segment with moderate degree of pain.